2017
DOI: 10.25186/cs.v12i1.1182
|View full text |Cite
|
Sign up to set email alerts
|

Cortes basais e substratos na formação de mudas clonais de cafeeiro canéfora

Abstract: Objetivou-se avaliar substratos e tipos de cortes nas estacas para produção de mudas clonais de cafeeiro canéfora. O experimento foi conduzido em casa de vegetação. As estacas foram obtidas a partir da porção média de ramos ortotrópicos padronizados. O experimento foi em esquema fatorial 2x7 com dois tipos de cortes nas estacas (corte basal retilíneo e em bisel) e sete substratos: solo, comercial, palha de café, maravalha (resíduo de madeira processada), comercial+palha de café (v:v), comercial+maravalha (v:v)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
1
1
Order By: Relevance
“…The TDM values observed in this study were higher than those found by Aquino et al (2017), while studying the production of clonal plantlets by the cutting method in Conilon coffee. Verdin Filho et al (2014) found a higher TDM in Conilon coffee by using a straight cut at the base of the stem cuttings, which favored the development of the root system and, consequently, of the seedling as a whole.…”
Section: Discussioncontrasting
confidence: 80%
“…The TDM values observed in this study were higher than those found by Aquino et al (2017), while studying the production of clonal plantlets by the cutting method in Conilon coffee. Verdin Filho et al (2014) found a higher TDM in Conilon coffee by using a straight cut at the base of the stem cuttings, which favored the development of the root system and, consequently, of the seedling as a whole.…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly to the variable NL, the DS values for the Conilon coffee seedlings grown on alternative substrates (4.28 to 4.48 mm) can be considered satisfactory (Table 3) when compared with other studies. When studying several types of basal sections and substrates in the growing of clonal seedlings of Conilon coffee, Aquino et al (2017) did not obtain DS values above 3.6 mm. It must be considered that the authors evaluated the seedlings at 100 days after planting, less time than that in this study (120 days).…”
Section: Residue Phmentioning
confidence: 87%
“…Neste contexto, garantir suporte inicial as plântulas, possibilitando um local firme para o desenvolvimento radicular e principalmente, favorecer as condições físico-química com as quantidades necessárias é a função principal de um bom substrato (SILVA et al, 2013), sendo sua composição, determinante na fase de 132 formação das mudas (AQUINO et al, 2017). Em vista da disponibilidade de resíduos alternativos para composição de substratos e os desafios para produção de mudas com qualidade a baixo custo, objetivou-se avaliar substratos alternativos para produção de mudas de cerejeiras.…”
Section: Introductionunclassified